2008
DOI: 10.1007/s10545-008-0912-z
|View full text |Cite
|
Sign up to set email alerts
|

Glutaric aciduria type I: outcome following detection by newborn screening

Abstract: Glutaric aciduria type I (GA I), a cerebral organic acidaemia with the potential for severe neurological consequences, can now be detected by tandem mass spectrometry newborn screening. Early detection with implementation of careful management strategies appears to lessen the likelihood of neurological damage. We assessed the outcome in all 10 GA I patients detected in New South Wales during the last decade. Three patients were detected clinically and 7 by newborn screening. Diagnosis was confirmed by detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 10 publications
3
40
0
Order By: Relevance
“…This applies especially to the estimation of cost, as the precise costs we incorporated in our decision analytic model can, of course, only be considered fully reliable for the specific scenario assumed. In contrast, the clinical evidence that our study is based on is not restricted to a single geographic setting but is derived from a variety of European countries and Australia [1,7,28,44,45]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This applies especially to the estimation of cost, as the precise costs we incorporated in our decision analytic model can, of course, only be considered fully reliable for the specific scenario assumed. In contrast, the clinical evidence that our study is based on is not restricted to a single geographic setting but is derived from a variety of European countries and Australia [1,7,28,44,45]. …”
Section: Resultsmentioning
confidence: 99%
“…The underlying cause is irreversible striatal injury resulting in a complex movement disorder with predominant dystonia [4-6]. Previous studies have shown that the outcome is mainly determined by a single crisis during infancy or childhood [3,7]. …”
Section: Introductionmentioning
confidence: 99%
“…In neonatally diagnosed patients, the frequency of brain injury was reduced to 0-36% compared to 90-95% in historical cohorts [7,12,18,[34][35][36][37]. Evidence-based treatment recommendations include (1) a low L-lysine diet (including the use of lysine-free, tryptophan-reduced amino acid supplements [AAS]), (2) L-carnitine supplementation, and (3) emergency treatment during intercurrent illness [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…A restrictive lysine and tryptophan diet, supplemented with L-carnitine and eventually, riboflavin, and a specific emergency treatment during intercurrent illness has significantly improved the outcome of pre-symptomatically diagnosed children [20][21][22] . Therefore, newborn screening for GA-1 has been implemented in some countries 5,7,23,24 . We describe two GA-1 patients illustrating the relevance of brain MRI for the diagnosis.…”
mentioning
confidence: 99%